2019
DOI: 10.1101/805127
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Natural selection drives population divergence for local adaptation in a wheat pathogen

Abstract: AbstractEvolution favors the emergence of locally-adapted optimum phenotypes that are likely to differ across a wide array of environmental conditions. The emergence of favorable adaptive characteristics is accelerated in agricultural pathogens due to the unique properties of agro-ecosystems. We performed a QST - FST comparison using 164 strains of Parastagonospora nodorum sampled from eight global field popul… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 83 publications
0
2
0
Order By: Relevance
“…Three expressed sequence tag (EST) derived SSR loci SNOD1, SNOD3, SNOD5, one minisatellite locus SNOD8 (Stukenbrock et al, 2005) and 16 newly developed SSR loci ( Supplementary Table S1) were used for genotyping. The new SSR markers were designed by Dr. Patrick C. Brunner at ETH Zurich based on the reference genome SN15 and alignments with genome sequences of 164 global strains of P. nodorum (Pereira et al, 2019). PCR was carried out with M13 tailed (Schuelke, 2000) fluorescent labeled primers ( Supplementary Table S1), PCR products were separated by capillary electrophoresis using an ABI3730 Gene Analyzer (Applied Biosciences) and a GeneScan 500 LIZ dye Size Standard from Applied Biosystems (Life Technologies), and the resulting data analyzed using Software: GeneMapper v.5 (Applied Biosystems).…”
Section: Ssr Analysismentioning
confidence: 99%
“…Three expressed sequence tag (EST) derived SSR loci SNOD1, SNOD3, SNOD5, one minisatellite locus SNOD8 (Stukenbrock et al, 2005) and 16 newly developed SSR loci ( Supplementary Table S1) were used for genotyping. The new SSR markers were designed by Dr. Patrick C. Brunner at ETH Zurich based on the reference genome SN15 and alignments with genome sequences of 164 global strains of P. nodorum (Pereira et al, 2019). PCR was carried out with M13 tailed (Schuelke, 2000) fluorescent labeled primers ( Supplementary Table S1), PCR products were separated by capillary electrophoresis using an ABI3730 Gene Analyzer (Applied Biosciences) and a GeneScan 500 LIZ dye Size Standard from Applied Biosystems (Life Technologies), and the resulting data analyzed using Software: GeneMapper v.5 (Applied Biosystems).…”
Section: Ssr Analysismentioning
confidence: 99%
“…This type of selection can only be possible when some of the phenotypic traits are favored by local environments such as climatic conditions or agricultural practices [58], for example, the density of fungicide application or trade-offs associated with fungicide resistant mutants [27,59]. Previous studies demonstrated that Q ST -F ST comparisons are a powerful approach to infer the importance of diversifying selection in the evolution of quantitative traits [44,60], and revealed that the evolutionary mechanism serves as main driver for the development of fungicide resistance and other ecological traits in pathogen populations including virulence, pesticide resistance, and temperature tolerance in Puccinia striiformis, Mycosphaerella graminicola, P. infestans, and Parastagonospora nodorum, [38,45,61,62]. On the contrary, stabilizing selection (Q ST < F ST ) was found to drive the adaptation of fungicide resistance in a barley pathogen Rhynchosporium commune [14].…”
Section: Sources Of Genetic Variation Contributing To Azoxystrobin Admentioning
confidence: 99%